Computational Identification of miRNAs and Temperature-Responsive lncRNAs From Mango (Mangifera indica L.) - Moh, Nann Miky Moh; Zhang, Peijing; Chen, Yujie; Chen, Ming (Frontiers in Genetics, 2021)
Mango is a major tropical fruit in the world and is known as the king of fruits because of its flavour, aroma, taste, and nutritional values. Although various regulatory roles of miRNAs and lncRNAs have been investigated in many plants, there is yet an absence of study in mango. This is the first study to provide information on ncRNAs of mango with the aim of identifying miRNAs and lncRNAs of mango and discovering of their potential functions by the interaction prediction of the miRNAs, lncRNAs and their target genes. In this analysis, 104 miRNAs and 7,610 temperature responsive lncRNAs were identified and the target genes of these ncRNAs were characterized. According to these results, newly identified mango ncRNAs, like other plant ncRNAs, have potential role in biological and metabolic pathways including plant growth and developmental process, pathogen defence mechanism, and stress responsive process. Moreover, mango lncRNAs can target miRNAs to reduce the stability of lncRNAs and can function as molecular decoys or sponges of miRNAs. This paper would provide the information about miRNAs and lncRNAs of mango and would help for the further investigation of the specific functions of mango ncRNAs and wet lab experiments.